The Cajun Renaissance and Cajun English. The Social, the Linguistic, the Imaginary - Olivier Glain (Anglophonia)
This paper focuses on Cajun English and the sociolinguistic implications of the Cajun Renaissance, a sociocultural movement that started in the 1960s in Southern Louisiana. Being either a monolingual French speaker or a bilingual French-English speaker was long at the heart of what it meant linguistically to be Cajun (Dubois and Horvath 2001). However, native-like competence in French almost completely vanished from Louisiana with the younger generations born during the 20th century, and Cajun English (CE) is now a full-fledged variety of English that allows the speaker to mark his/her Cajun identity (Dubois and Horvath 2000, 2008). One of the key questions linked to the Cajun Renaissance is therefore to determine to what extent (Louisiana) French played a part in the emergence of this identity-driven variety. After explaining the historical background of language in Louisiana, I propose a description of the main features of Louisiana French and Cajun English to see how French in general, and Louisiana French in particular, have had an influence upon Cajun English. This description is based on the existing literature and the segmental and suprasegmental analysis of various recordings, including the Cajun English Corpus (Carmichael 2013). I argue that Cajunness very effectively manifests itself linguistically through the stance taken by CE speakers, either through the long-term accretion of stance (Du Bois 2007) that is due to the Cajun context and the speaker’s habitus, or through the temporary projection of Cajunness through stancetaking, which implies that the speaker positions him/herself relative to an addressee. One particularly interesting manifestation of stancetaking is found in the popular Louisianan practice of telling Boudreaux and Thibodeaux jokes, recordings of which can be found in the Cajun English Corpus. Finally, in a discussion on Cajun English and the Cajun identity based on speakers’ processes of self-identification, I argue that the Cajun collectivity can best be described as an ideological community, whose language variety has emerged from complex interactions within the speakers’ linguistic imaginaries (Houdebine 1982) and has been influenced by a powerful social imaginary (Castoriadis 1975).